2014
DOI: 10.1007/s10661-014-3883-6
|View full text |Cite
|
Sign up to set email alerts
|

Land suitability assessment for wind power plant site selection using ANP-DEMATEL in a GIS environment: case study of Ardabil province, Iran

Abstract: Wind energy is a renewable energy resource that has increased in usage in most countries. Site selection for the establishment of large wind turbines, called wind farms, like any other engineering project, requires basic information and careful planning. This study assessed the possibility of establishing wind farms in Ardabil province in northwestern Iran by using a combination of analytic network process (ANP) and decision making trial and evaluation laboratory (DEMATEL) methods in a geographical information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 27 publications
1
73
0
6
Order By: Relevance
“…For example, the elderly can either be highly vulnerable or less vulnerable depending on their income. To overcome this problem, we used the ANP method, which has a network structure with bilateral relationships, enabling inner and outer dependences between criteria to be considered (Azizi et al, 2014).…”
Section: Reflections On the Ahp And Anp Model Resultsmentioning
confidence: 99%
“…For example, the elderly can either be highly vulnerable or less vulnerable depending on their income. To overcome this problem, we used the ANP method, which has a network structure with bilateral relationships, enabling inner and outer dependences between criteria to be considered (Azizi et al, 2014).…”
Section: Reflections On the Ahp And Anp Model Resultsmentioning
confidence: 99%
“…Latinopoulos and Kechagia [26] used GIS-based, multi-criteria assessment for wind project location selection in Greece; they considered economic, technological, social, and environmental factors as criteria with substantial numbers of sub-criteria. Azizi et al [27] used the environmental, technical, and economic factors in wind power plant site selection. Al-Yahyai et al [28] have also considered various dimensions to evaluate the suitability of land for wind projects site selection in Oman, including the distance to roads, slope, historical locations, nature, wind power, and energy demand.…”
Section: Factor Analysis (Fa)mentioning
confidence: 99%
“…Development cost [39,40] Public health and community impact [41] Wind data availability [27,42] Government policies [43] Effect on economic development of nearby areas [31] On-grid accessibility [29][30][31] Wildlife and habitat impact [42] Climate conditions [29] Land acquisition [39,40] Distance from residential areas [27,30,31] Road availability [28][29][30][31] Area of flatland and without forest cover [27,29] Skilled manpower availability [39,40] Relocation and rehabilitation [42] Effect on employment and agriculture [44] Social acceptance [43] In summary, the main criteria considered in this study (i.e., economic, technical, environmental, political, and social factors) are vital aspects of wind power plant development in Pakistan.…”
Section: Economic Factormentioning
confidence: 99%
“…In this study, the review of existing literature (25 current authoritative studies [1][2][3][4][5]29,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]) was first carried out. From the analysis of the literature, it can be observed that the current indicators for wind and solar power generation sites can be mainly divided into seven aspects: natural resources, economic factors, technical factors, traffic conditions, geographical factors, social factors and environmental factors.…”
Section: Location Index Of Wind-solar Power Generationmentioning
confidence: 99%